Senegal : Looking for Work - The Road to Prosperity, Volume 2. Annexes - World Bank (Washington, DC, 2012)
This economic study comprises four parts. Part one analyzes the economic performance of Senegal with a view to understanding how an efficient labor market is an essential (but not sufficient) condition for achieving sustained and shared growth. This section focuses on the role of the labor market in (i) promoting a virtuous circle between economic growth and poverty reduction through equitable distribution of earned income (which is the main source of income for the Senegalese population, accounting for up to 3/4 of total resources, according to the results of the first household survey ESAM-I); and (ii) creating a competitive and dynamic private sector, as the wage bill accounts for a predominant share of the costs of Senegalese companies. The second part of the study focuses on the perspective of companies motivated by the objective of maximizing labor productivity to become as competitive as possible. The third part of the study presents the perspective of workers or that of the search for job security. The objective is to examine in detail whether the labor market is capable, not only of offering jobs to the majority of the population, but also whether this job provides sufficient income and conditions that allow workers to live free of poverty. The fourth and final part will summarize lessons learned from the previous parts.